2015
DOI: 10.5530/jyp.2015.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Depression as Comorbidity in Diabetes Mellitus Patients using Beck Depression Inventory II (BDI II) Scale

Abstract: Objective:The objective was to assess depression as comorbidity among patients of diabetes mellitus (DM) using Beck Depression Inventory II (BDI II) scale. Materials and Method: A cross sectional survey was conducted in Pakistan for 3 months targeting patients of diabetes mellitus DM and assessing their depression as a comorbidity using BDI II questionnaire. Data analysis was carried out using SPSS version 20. Descriptive statistics, cross tabulation and Chi square (X 2 ) tests were employed. Results: Majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…This also eliminated selection bias. Female patients were reported in more numbers in previous studies . They were more likely to participate as compared to the male patients.…”
Section: Methodsmentioning
confidence: 81%
“…This also eliminated selection bias. Female patients were reported in more numbers in previous studies . They were more likely to participate as compared to the male patients.…”
Section: Methodsmentioning
confidence: 81%
“…Diabetes mellitus (DM) is a type of chronic illness that requires careful management with medications to keep blood glucose level in recommended range (Abahussain and El-Zubier, 2005;World Health Organization, 2010;Abbas et al, 2015). The disease could result in micro and macro vascular complications that have serious short and long-term repercussions.…”
Section: Introductionmentioning
confidence: 99%
“…Patient adherence to anti diabetic medication therapy results in better control of disease and may help to keep Hb A1c in recommended range (Al Dawish et al, 2016). There is a plethora of studies that highlight the importance of adhering to medications in type 2 diabetes mellitus (Al-Nozha et al, 2004;Abahussain and El-Zubier, 2005;Abbas et al, 2015;Al Dawish et al, 2016). However, it is imperative to improve patients' disease knowledge to achieve high adherence to therapy (Yeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of numerous studies have shown that there is a mutual link between hypertension and depression, there are still scarce data on the overall prevalence of depression in patients with hypertension [8]. Most of the time, depression is not considered an important factor, often ignored and left untreated [9]. To muddle through the everyday tribulations involved in supervision and handling of disease is barely challenging for patients but parallel for caretakers and healthcare professionals [10].…”
Section: Introductionmentioning
confidence: 99%